EXPLORING PHYSICAL ACTIVITY PATTERNS DURING PREGNANCY IN MOTHERS WITH CESAREAN DELIVERY - Mariam, Nina; Marfuah, Dewi; Mutiar, Astri; Nurdina, Gina (DPW PPNI Provinsi Jawa Barat, 2024)
Background: The quantity of babies born by the cesarean delivery procedure in Indonesia is 17.6%. One way to prevent complications from childbirth is to do physical activity because doing regular and directed physical activity can maintain the health of the mother and fetus during pregnancy. Methods: The study, conducted in a private hospital in Bandung, involved 81 respondents aged 40-18 years old, who were categorized based on factors such as maternal age, gestational age, education, occupation, obstetric status, and physical activity during pregnancy. Results: Pregnant women's activities were analyzed, with a total average score of 325.72, with the highest score being 941.73. The highest scores were found in household physical activity, occupational activity, exercise activity, transportation activity, and sedentary activity. The highest score was in work activities, with a score of 450.50, while the lowest scores were in work activities, exercise/sports, transportation, and sedentary activities. Conclusion: Household activities are the highest activities and the lowest activities are sports.